Case report: A case of fetal umbilical vein varix presenting disseminated intravascular coagulation, polycythemia, and neonatal hepatitis in an extremely low birth weight infant - Sekiguchi, Mariko; Mukai, Takeo; Shitara, Yoshihiko; Kashima, Kohei; Seyama, Takahiro; Kumasawa, Keiichi; Takahashi, Naoto (Frontiers in Pediatrics, 2023)
Reports on the clinical course of fetal umbilical vein varix in premature infants are limited. We report a case of an extremely low body weight infant with intra-abdominal umbilical vein varix who developed disseminated intravascular coagulation, polycythemia, and hyperbilirubinemia after birth; late-onset neonatal hepatitis; and fetal thrombotic vasculopathy confirmed by placental histopathology. Ultrasonography after birth showed a dilated portion of the umbilical vein at the hepatic hilum with thrombi inside. We speculate that the umbilical vein varix caused the fetal thrombotic vasculopathy, and the presence of umbilical vein varix and fetal thrombotic vasculopathy in combination with prematurity caused coagulopathy, polycythemia, hyperbilirubinemia, and hepatitis. Despite the favorable outcomes reported in the literature, premature infants with umbilical vein varix may require careful observation and management for coagulopathy and late-onset hepatitis. Furthermore, placental histopathology could aid in the understanding of various clinical outcomes in infants with umbilical vein varices.